Country Policy Framework for Cooperative Approaches Under Article 6.2 - World Bank (World Bank, Washington, DC, 2021)
Policy framework has been drafted on a unilateral basis for a Party to declare its preferred approach towards implementing a cooperative approach under Article 6.2. The policy framework is intended to provide the minimum legal foundation required to give Parties (including private sector entities) the necessary certainty regarding their rights and obligations as participants to the cooperative approach, including the ability to enforce cross-border contractual arrangements. The policy framework is intended to facilitate negotiations and subsequent agreement between two or more Parties, and the policy framework does not in itself create an effective and binding cooperative approach between Parties. The policy framework is accompanied by several schedules to the policy framework, which play an integral role in setting out the specific requirements. It is intended that these schedules contain the detailed and technical information related to, among other things, environmental integrity, sustainability requirements, approved sectors and activities, and approved standards and methodologies, for the purposes of implementing a cooperative approach. The development of schedules will also benefit from inputs from various technical experts and consultations in platforms such as the climate market club, alongside the final article 6.2 guidance.